Serum overexpression of microRNA-454-3p in patients with colorectal cancer and determine its correlation with pathological characteristics - Setareh Naeimi; Elahe Aliasgari; Faranak Jamshidian (Acta Scientiarum. Health Sciences)
This study aimed to evaluate serum overexpression of microRNA-454-3p in patients with colorectal cancer and determine its correlation with pathological characteristics. Exosomes isolated from the serum of 40 CRC patients and 30 healthy subjects by Exoquick kit solution, were characterized using SEM. The expression of miR-454-3p was assessed in both healthy and CRC patients using the RT-PCR method. Then, by ROC analysis, the capability of this microRNA as a biomarker was determined. P-value < 0.05 was determined as significant. The results of the study showed that the rate of microRNA-454-3pexpression in the samples of CRC patients was significantly higher than in the control population (p < 0.01). Also, the expression of microRNA-454-3pin stage III of the disease showed a significant increase, compared to stages I and II (p < 0.05).miR-942-5p expression in CRC patients with lymphatic metastasis was significantly higher than those with no metastasis to their lymph nodes (P-value < 0.05). Also, the sensitivity and specificity of miR-454-3p were found to be 79 and 99%, respectively (with an area under the ROC curve [AUC] of 0.89). It seems that the increased expression of the microRNA-454-3p gene has a role in the pathogenesis of CRC and also the expression of this gene is associated with the stage of cancer.